(untitled) (Sociología y tecnociencia, 2021)
The current article analyzes the relationship between the involvement of the ‘locals’ in peacebuilding processes and development of the new multi-concepts of peace. In the first part, we present the concept of peace in the international relations (IR) discipline and how, in the 20th century, peace studies were established as a discipline within IR until it became an independent discipline separated from IR. The current article also analyzes critically how the involvement of the ‘locals’ has influenced the contemporary global concept of peace and conflict. In the second part, we present two cases: the Ambon conflict in Indonesia and the recent history of conflicts in Mozambique.